Photothermal effect in graphene-coated microsphere resonators. (19th June 2018) - Yuan, Chenzhi; Zhang, Wei; Huang, Yidong
Abstract: In this study, graphene-coated silica microsphere resonators with Q values of ∼10 5 are fabricated. After wet transfer of a graphene layer onto the surface of the microsphere, the deterioration of the Q value due to the graphene layer is overcome by a laser treatment. The photothermal effect in the fabricated resonators is investigated experimentally. Using a control-probe scheme, the resonance shift by the photothermal effect is demonstrated, with a high tuning slope. Optical bistability is also observed, with a low threshold and high switching contrast. The experimental results show that the graphene-coated microsphere resonator is a promising platform to investigate the interaction between graphene and light field.